THE USE OF DEIXIS IN THE TEXT OF THE KING CHARLES III’S SPEECH IN THE KING CORONATION - Oktaviani, Hilda Izza; Wafa, Hosnol; Andayani, Sri; Tjahyadi, Indra (JURNAL LITERASI, 2023)
This study analyzes the transcripts of King Charles III’s speech. The purpose of this study is to find out what deixis is used in King Charles III’s speech. Deixis is a form of language in the form of words and others that function specifically outside of language. In other words a form of language can be said to be deixis if the reference moves or changes according to who is the speaker and also depends on the time and place. So, in other words, deixis are words that do not have fixed reference. The scope of this research is pragmatic. The theory used is based on the theory by Levinson which explains the five deixis. Levinson’s theory is used in this study because Levinson explains personal, time, place, social, and discourse deixis types in more detail and comprehensively compared to other theories. This research is qualitative and descriptive method. Data collecting technique is the observation method. This study focuses on data collection, namely written documents in the form of text. The data source for this study is the transcript of King Charles’s speech “Deixis Analysis of King Charles III’s Speech In The King Coronation”.To analyze the data of this study, after collecting data from speech transcripts, the data of this study analyzed as follows: first, identify some words or phrases that are included in deixis expression. Second, the classification of predetermined deixis clauses based on criteria. Third, the data analyzed based on Levinson’s theory in 1983 which defined the types of deixis, namely: Person Deixis, Place/Spatial Deixis, Time/Temporal Deixis, Social Deixis, and Discourse Deixis. The latter determines the type of Deixis used in King Charles’s speech. The validity of qualitative research in this study can be seen by re-checking.There are two methods and techniques for presenting data analysis, namely formal and informal method. This study has 5 types of deixis used. There are 109 utterances using Person Deixis, 3 utterances using Place Deixis, 8 utterances using Time Deixis, 9 utterances using Social Deixis, and 12 utterances using Discourse Deixis.